Standardized corporate social responsibility disclosure, assurance, and real earnings management: evidence from developing countries - Eko Budi Santoso; Basuki Basuki; Isnalita Isnalita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to present empirical evidence on the effect of social responsibility disclosure on real earnings management and the role of assurance in this relationship. This is based on a paradox, i.e., companies that publish standardized corporate social responsibility disclosures to project ethical business practices are also associated with accounting and financial scandals.Design/Methodology/Approach: This study was conducted on non-financial sector companies in developing countries that are members of ASEAN-4, namely Indonesia, Malaysia, Thailand, and the Philippines, which issued GRI-based social responsibility disclosures in the period 2013-2019, amounting to 285 companies with a total of 859 observations.Research findings: The results demonstrated that companies with standardized social responsibility disclosures tend to reduce their real earnings management practices. However, the assurance variable mitigates the negative effect of corporate social responsibility on real earnings management, implying that assurance provides false credibility. In an additional analysis, the samples were grouped based on board structure. The findings of this study are consistent with two-tier board structures, suggesting that a one-tier system provides better information quality.Theoretical contribution/Originality: The originality of this study lies in a comprehensive measurement of social responsibility disclosure variables using an index that gauges a combination of accountability and performance aspects. Furthermore, this study takes into account assurance as a variable representing the credibility of information, which surprisingly moderates the negative effect of social responsibility disclosure on real earnings management.Practitioner/Policy implication: The findings of this study underscore the importance of standardized social responsibility disclosure in mitigating managerial opportunistic behavior. The findings also highlight the need to enhance the assurance function to prevent its use as an opportunistic management tactic.